EFEKTIVITAS MODEL PEMBELAJARAN MIND MAPPING DISERTAI STRATEGI HEURISTIK KRULIK DAN RUDNICK DALAM PEMECAHAN MASALAH - Patimah Patimah; Zubaidah R; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe aimed of this research was to knowed how the effectiveness of mind mapping learning model with heuristic strategy Krulik and Rudnick in problem solving on probability materials in SMA. The method used is pre-experiment method, while the subject are 32 students of class XI IPA4 SMAN 5 Pontianak. The technique used in data collection is a measurement technique. Data collection in the form of observation sheet for learners. Data were collected and analyzed by calculating percentages and mean values. This study was conducted 3 times of meetings. the result of the data analysis showed that student activity during the learning process obtained an average of 64,91% which is categorized as quite and posttest result of students' math problem solving ability obtained 61,13 which is categorized well. Based on the research finding, it can be concluded that mind mapping learning model with heuristic strategy of Krulik and Rudnick was effective in teaching on probability material in class XI IPA4 SMAN Pontianak. Keywords:  Mind Mapping Learning Model, The Krulik and Rudnick Heuristic strategies, Problem-Solving